2022
DOI: 10.1111/nph.18183
|View full text |Cite
|
Sign up to set email alerts
|

The Rysto immune receptor recognises a broadly conserved feature of potyviral coat proteins

Abstract: Summary Knowledge of the immune mechanisms responsible for viral recognition is critical for understanding durable disease resistance and successful crop protection. We determined how potato virus Y (PVY) coat protein (CP) is recognised by Rysto, a TNL immune receptor. We applied structural modelling, site‐directed mutagenesis, transient overexpression, co‐immunoprecipitation, infection assays and physiological cell death marker measurements to investigate the mechanism of Rysto–CP interaction. Rysto associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…In plants, Ry sto interacts directly with PVY CP and the correct folding of the CP pore is essential for interactions. The Ry sto can recognize the CPs of a minimum of 10 important viruses with a similar core region and enable Solanaceae and Brassicaceae resistance against the plum pox virus and turnip mosaic virus [ 2 , 17 ]. The Ry chc on Chromosome IX from the wild species S. chacoense has not been cloned.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, Ry sto interacts directly with PVY CP and the correct folding of the CP pore is essential for interactions. The Ry sto can recognize the CPs of a minimum of 10 important viruses with a similar core region and enable Solanaceae and Brassicaceae resistance against the plum pox virus and turnip mosaic virus [ 2 , 17 ]. The Ry chc on Chromosome IX from the wild species S. chacoense has not been cloned.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 ] The properties of host factors involved in the cell‐to‐cell trafficking of potyviruses and their interaction with CP are gradually being revealed. [ 33 ] Wherein DnaJ‐like proteins from tobacco, named NtCPIPs, are mainly involved in the intercellular movement of viruses and lead to the effective diffusion of PVY in host plants after interacting with CP. Meanwhile, mutations in the core region of CP abolish its interactions with NtCPIPs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on tomato and rice NLRs Xo1 and Bs4 have shown that the recognition of closely related TAL effectors can involve their structural similarity rather than their transcriptional activity (Schornack et al ., 2006 ; Triplett et al ., 2016 ). Also, a recent study on recognition by the TIR–NLR Ry sto showed that structurally conserved features in the coat protein of multiple potyviruses trigger its activation (Grech‐Baran et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%